The Green Food Supply Chain: Factors Affecting Food Distributor’s Sustainability Through Positive WOM - Annas, Mohammad; Humairoh (Jurnal Manajemen, 2023)
The research intended to uncover factors affecting customers using and repeating orders and transactions with logistics companies in five major logistics hubs in Indonesia. The quality of the food delivered, the service provided, and perceived value significantly impact logistics user satisfaction and bring them back in future transactions. Word of Mouth construct took place as a trigger and supported the fact that it pushed the customers to come back again and take the same logistics service. The result showed that logistics customer satisfaction has a positive influence on positive word of mouth, where the P value was < 0.05 so that when consumers are satisfied with their experience in using the services of a logistics company, it will increase consumers in recommending friends or relatives to take the same services. Positive word of mouth positively influences repurchase intention, where the P value was <0.05, so when consumers recommend friends or relatives to use logistics services, it will increase repurchase intention.